DNAP: Dynamic Nuchwezi Architecture Platform - A New Software Extension and Construction Technology - Lutalo, Joseph Willrich; Eyobu, Odongo Steven; Kanagwa, Benjamin (IEEE, 2020)
The need to improve or build new software systems to solve new and old business challenges is a persistent challenge in the software consumer and development industry, yet costly. To minimize these costs, the construction method should be designed with the following qualities in mind; software portability, extensibility, and simplicity. To achieve these qualities, this paper proposes the Dynamic Nuchwezi Architecture Platform (DNAP), which is a new software construction and extension technology. DNAP offers a visual programming paradigm with a capability of generating production-ready business automation software for both mobile and web. It also offers a simple mechanism for the extension of existing softwares using embeddable components. To evaluate and justify DNAP, eight Software Operating Environment (SOE) metrics have been developed and together with the SOE model, are used to contrast DNAP against four alternative software construction technologies namely; Android Platform, .NET Framework, Java SE Platform and Python. The performance evaluation results show that DNAP offers an average of 33% reduction in software construction complexity and an 11% enhancement in language efficiency when compared to alternative technologies.
Keywords: Software Construction Optimization; Visual Programming; Cross-Platform Development; Platform Engineering; Mini-Programs; Software Metrics